2021
DOI: 10.1177/01926233211042270
|View full text |Cite|
|
Sign up to set email alerts
|

Histology Atlas of the Developing Mouse Placenta

Abstract: The use of the mouse as a model organism is common in translational research. This mouse–human similarity holds true for placental development as well. Proper formation of the placenta is vital for development and survival of the maturing embryo. Placentation involves sequential steps with both embryonic and maternal cell lineages playing important roles. The first step in placental development is formation of the blastocyst wall (approximate embryonic days [E] 3.0-3.5). After implantation (∼E4.5), extraembryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 132 publications
(471 reference statements)
2
36
0
Order By: Relevance
“…It seems likely that an early inoculation during embryo implantation (4.5 DG) period [ 55 , 56 ] allows an effective colonisation of placental envelops, showing a progressive multiplication of 16M and Rev1, peaking at the end of gestation. It has been reported that Brucella localises preferentially in TGC [ 11 , 25 ], which are mainly placed at the junction and labyrinth layers [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems likely that an early inoculation during embryo implantation (4.5 DG) period [ 55 , 56 ] allows an effective colonisation of placental envelops, showing a progressive multiplication of 16M and Rev1, peaking at the end of gestation. It has been reported that Brucella localises preferentially in TGC [ 11 , 25 ], which are mainly placed at the junction and labyrinth layers [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The proliferation of TGC during these first stages of placental development seems to favour Brucella multiplication. Interestingly, 16M and B. suis bv2 counts decreased at 9.5 DG (5 days PI), the stage at which maternal blood enters the labyrinth [ 56 ]. This phenomenon could be explained by the increased irrigation of placental tissues facilitating cell-mediated immune response, which is followed by the marked cytokine release at 5 days PI.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first analysis of mouse placentae at two gestational time points that demonstrates the effect of HFD on lipidomic profiles. Our first measurement at E12.5 corresponds to the appearance of the first definitive placenta, while the second measurement point near E18.5 represents a fully functioning organ nearing the end of its lifespan, preparing for parturition ( 27 , 28 ). The visibly greater concentration of FC between the two diet arms at the early time point was not present by E18.5.…”
Section: Discussionmentioning
confidence: 99%
“…This should not be surprising, since vessel development is similar in embryonic and extra-embryonic tissue [32][33][34] . Given that that by approximately E12.5 the de nitive placenta is mature 35 and the E12.5 embryos and extra-embryonic tissue appeared grossly normal, we conclude that embryonic lethality later than E12.5 is unlikely to have placental defects as a primary cause. We hypothesize therefore that lack of SAMD1 causes roughly simultaneous changes in the embryo, the yolk sac and the placental vasculature.…”
Section: Discussionmentioning
confidence: 76%